Teachers' Perception on Local Curriculum in School Education of Nepal (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
This research paper aims at exploring the teachers' perception and their conceptual understanding on local curriculum, importance of local curriculum and local curriculum development process in school education of Nepal. For this, the interpretive paradigm was adopted to explore the subjective realities concerned with the central phenomenon. Within this process, this qualitative phenomenological study collected the intense information through the in-depth interviews with the selected community schools' basic level teachers. Based on the information, three themes have been developed for presenting the results and discussion. The major findings of this study are that the teachers positively perceived the local curriculum for preserving the local knowledge, cultures as well as the tourism areas of a community. The teachers also perceived that the teachers, parents and community participation is also essential during the local curriculum development process as well as selection of local subject. Apart from these shining areas, they did not develop the local curriculum at school or local level. Instead of the local subject, English and computer subject were implemented in the name of optional subjects in grade one to five and six to eight respectively.